2021
DOI: 10.31234/osf.io/yeufs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bridging the technological divide: Stigmas and challenges with technology in clinical studies of older adults.

Abstract: The COVID-19 pandemic has increased adoption of remote assessments in clinical research. However, longstanding stereotypes persist regarding older adults’ technology familiarity and their willingness to participate in technology-enabled remote studies. We examined the validity of these stereotypes using a novel technology familiarity assessment (n = 342) and with a critical evaluation of participation factors from an intensive smartphone study of cognition in older adults (n = 445). The technology assessment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…demand characteristics, "white coat" testing effects), bolster sample size and diversity, and make participation more accessible and inclusive for individuals who may otherwise be unable to come into the laboratory or clinic. Indeed, interest in smartphone studies is growing and several studies have demonstrated the feasibility and validity of smartphone-based assessments for use in older adults and individuals with preclinical AD (Güsten et al, 2021;Hassenstab et al, 2020;Lancaster et al, 2020;Mackin et al, 2018;Öhman et al, 2021;Papp et al, 2021;Nicosia et al, 2021;Wilks et al, 2021), as semi-structured interviews with the participant and an informant (i.e., family member or friend).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…demand characteristics, "white coat" testing effects), bolster sample size and diversity, and make participation more accessible and inclusive for individuals who may otherwise be unable to come into the laboratory or clinic. Indeed, interest in smartphone studies is growing and several studies have demonstrated the feasibility and validity of smartphone-based assessments for use in older adults and individuals with preclinical AD (Güsten et al, 2021;Hassenstab et al, 2020;Lancaster et al, 2020;Mackin et al, 2018;Öhman et al, 2021;Papp et al, 2021;Nicosia et al, 2021;Wilks et al, 2021), as semi-structured interviews with the participant and an informant (i.e., family member or friend).…”
Section: Introductionmentioning
confidence: 99%
“…Feasibility and Tolerability Measures. Technology familiarity was assessed with a novel measure described in Nicosia et al (2021). Briefly, the assessment combined objective measurements of technology knowledge (technology-related icon recognition) and self-reported ratings of (1) the frequency with which they perform certain smartphone tasks; and (2) how difficult it would be for them to perform various technology-related tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation